Enabling collaborative synthesis in multi-partner programmes - Cochrane, Logan; Cundill, Georgina (Development in Practice, 2018)
Multi-partner consortia have emerged as an important modality for know ledge generation to address complex sustainability challenges. Establi shing effective multi-partner consortia involves significant investmen t. This article shares lessons from the Collaborative Adaptation Resea rch Initiative in Africa and Asia (CARIAA), which aims to support poli cy and practice for climate change adaptation through a consortium mod el. Key lessons include the need to facilitate collaborative spaces to build trust and identify common interests, while accepting that this is not a guarantee of success; the importance of programmatic leadersh ip to achieve synthesis; and the value of strategic planning in suppor ting motivation and alignment between partners.